The synthesis of some novel stilbene dimers incorporating diamide tethers: studies in single electron transfer oxidation (FeCl3) - Alehashem, Maryam Sadat; Ariffin, Azhar; Al-Khdhairawi, Amjad Ayad Qatran; Thomas, Noel Francis (Royal Society of Chemistry, 2018)
The FeCl3 oxidative cascade reaction of the acetamido stilbene 1 which we reported some years ago produced the first atropodiastereomeric indolostilbene hybrid 3. By contrast, recent investigation of the oxidation of the stilbene succinamide dimer 72 (FeCl3/CH2Cl2) appears, on the basis of spectroscopic evidence, to have produced the bridged macrocyclic indoline 73.